2016
DOI: 10.1007/s00774-016-0794-3
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity may be a potent regulator of bone turnover biomarkers in healthy girls during preadolescence

Abstract: This study investigated the effects of different levels of habitual physical activity (PA) assessed by pedometry on bone turnover markers of preadolescent girls according to a cross-sectional experimental design. Sixty prepubertal girls of similar chronological age, bone age, maturity level, and nutritional status were assigned to a low PA (LPA; n = 25), a moderate PA (MPA; n = 17), or a high PA (HPA; n = 18) group. Dual-energy X-ray absorptiometry was used to measure areal bone mineral density (BMD) and bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
8
1
Order By: Relevance
“…Bone turnover markers have been used in several studies to assess the short-term effect of exercise on bone metabolism. Studies have focused on prepubescent girls [ 99 , 100 ], pre-menopausal [ 101 , 102 , 103 , 104 , 105 ], and post-menopausal women [ 106 , 107 , 108 , 109 ], and have looked at the short- and long-term biomarker response to exercise. Of particular interest to monitoring the biological response to mechanical loading is sclerostin, the protein product of the SOST gene in osteocytes.…”
Section: Emerging Areas Of Research About Exercise and Women’s Bonmentioning
confidence: 99%
“…Bone turnover markers have been used in several studies to assess the short-term effect of exercise on bone metabolism. Studies have focused on prepubescent girls [ 99 , 100 ], pre-menopausal [ 101 , 102 , 103 , 104 , 105 ], and post-menopausal women [ 106 , 107 , 108 , 109 ], and have looked at the short- and long-term biomarker response to exercise. Of particular interest to monitoring the biological response to mechanical loading is sclerostin, the protein product of the SOST gene in osteocytes.…”
Section: Emerging Areas Of Research About Exercise and Women’s Bonmentioning
confidence: 99%
“…(17) The bone resorption findings of the present study are in line with a previous longitudinal study in peripubertal girls that did not find significant differences in bone resorption between gymnasts, runners, and controls after 1 year. (28) Also, it has been previously shown that bone remodeling might be increased because of participation in high-intensity weight-bearing activities during puberty, (56,57) which might explain the increased bone remodeling in footballers.…”
Section: Longitudinal Bmc Acquisition Between Groupsmentioning
confidence: 99%
“…Childhood and adolescence represent periods when girls and boys can achieve optimal bone mass for the prevention of osteopenia and osteoporosis during adulthood. Optimization of bone mass is determined by genetic factors but also by modifiable environmental factors, such as physical activity and diet [ 32 ]. Although bone mineral density is considered an important, precise, and valid measurement, BMD does not reflect the dynamic changes the bone has undergone.…”
Section: Discussionmentioning
confidence: 99%